Waterproofing materials for flat roof / Ahmad Syukri Abdul Rahman - Abdul Rahman, Ahmad Syukri (Faculty of Architecture, Planning and Surveying, 2008)
Waterproofing is a building structure which is a critical element of its design and construction. Because of the damaging effect of water, particular attention should be given in selecting quality waterproofing material to provide the proper in place performance. Waterproofing material’s life is shorter than building’s life. This study is to identify the source of the problem of waterproofing failure, the type of waterproofing material that frequently used and the most suitable material use for the flat roof. All the information is given by the maintenance department of every case study. The data collected the information about the type of material in use, and the history maintenance, basically to find out the method construction design and effective of material. Rubberized Asphalt sheet membrane is frequently used for the flat roof area followed by PVC/HDPE sheet membrane and lastly bitumen and the cost of PVC material is highest than the Rubberized and bitumen material. The conclusion of the findings; the rubberized asphalt sheet membrane is the best material to use for the flat roof. It can bee seen from the bar chart, that the rubberized asphalt has more good characteristic and the cost is also reasonably compared to other materials.